2020
DOI: 10.3390/mi11030319
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gas–Wall and Gas–Gas Interactions on the Accommodation Coefficients for Rarefied Gases: A Molecular Dynamics Study

Abstract: Molecular dynamics (MD) simulations are conducted to determine energy and momentum accommodation coefficients at the interface between rarefied gas and solid walls. The MD simulation setup consists of two parallel walls, and of inert gas confined between them. Different mixing rules, as well as existing ab-initio computations combined with interatomic Lennard-Jones potentials were employed in MD simulations to investigate the corresponding effects of gas-surface interaction strength on accommodation coefficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The gas-gas and gas-solid interactions are modeled by the Lennard-Jones (LJ) potential and the potential parameters are listed in Table I. It is noteworthy to mention that in the atomistic study of the GSI, the pair potential parameters employed to describe the interaction strength at the gas-solid interface are of prominent importance [36,37]. It has been shown that the interaction potentials based on mixing rules cannot accurately describe GSI, and the quantum calculations based on pair potentials are the most reliable ones to study the GSI at the molecular scale [36,38,39].…”
Section: A MD Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The gas-gas and gas-solid interactions are modeled by the Lennard-Jones (LJ) potential and the potential parameters are listed in Table I. It is noteworthy to mention that in the atomistic study of the GSI, the pair potential parameters employed to describe the interaction strength at the gas-solid interface are of prominent importance [36,37]. It has been shown that the interaction potentials based on mixing rules cannot accurately describe GSI, and the quantum calculations based on pair potentials are the most reliable ones to study the GSI at the molecular scale [36,38,39].…”
Section: A MD Simulationmentioning
confidence: 99%
“…It is noteworthy to mention that in the atomistic study of the GSI, the pair potential parameters employed to describe the interaction strength at the gas-solid interface are of prominent importance [36,37]. It has been shown that the interaction potentials based on mixing rules cannot accurately describe GSI, and the quantum calculations based on pair potentials are the most reliable ones to study the GSI at the molecular scale [36,38,39]. Therefore, in this work the gas-wall interaction potential parameters are calculated based on existing quantum ab initio computations [40].…”
Section: A MD Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…These effects will be more prominent at higher energies and must be accounted for by an inclusion of exchange terms in the Hamiltonian [35,36,37]. An even fuller approach would be to replace the Coulomb potential with more realistic interactions [38,39,40].…”
Section: Prospects and Limitationsmentioning
confidence: 99%
“…Understanding gas–solid surface interactions under rarefied conditions is of primary importance for efficient modeling of gas flows and heat transfer in microsystems. Mohammad Nejad et al [ 1 ] used a molecular dynamics approach to simulate the behavior of two monoatomic gases, argon and helium, confined between two gold surfaces, kept at different temperatures in order to determine the corresponding energy and momentum accommodation coefficients. They showed that the pressure level has a minor influence on the accommodation coefficients value.…”
mentioning
confidence: 99%